The Comparison of the Effectiveness of Parent-Child Interaction Training and Adler-Dreikur Parenting Training on Children's Clinical Syndrome - Safdar Rostami; Hasan Toozandehjani; Hamid Nejat (Shahid Beheshti University of Medical Sciences, 2019)
Background and Objective: Extensive efforts have been made in the field of child psychotherapy to involve parents in the treatment of children with psychiatric pathology syndrome. The present study was conducted to investigate and compare the effectiveness of Parent-Child Interaction Training and Adler-Dreikur Parenting Training on children's clinical syndrome. Materials and Methods: The present study was of semi-experimental design with pre-test, post-test, and control group. The statistical population included divorced mothers who were referred to counseling centers of 11th District in Mashhad city in 2017, among whom 60 mothers with their children were selected through purposeful sampling method and randomly divided into three groups of experimental and control groups. The Parent-Child Interaction group (N=20) received 15 sessions and Adler-Dreikurs group participants underwent 10 training session, the control group did not receive any intervention. For assessing of clinical syndrome, Child Behavior Checklist (CBCL) was used in pre, post, and follow-up stages. Data analyzed using repeated measure variances via SPSS software version 21. Results: The mean (SD) age of mothers and children in three groups were 32.2(4.5) and 9.0(1.5) in Parent-Child Interaction group, 33.9(3.7) and 9.6(1.5) in Adler-Dreikurs group, and 32.7(4.2) and 9.0(1.4) in the control group. The mean (SD) score of clinical syndrome in the Parent-Child Interaction group was 170.5 (9.6) in the pre-test, which varied to 153.4 (13.0) in the post-test, and 155/9(9/0) in the follow-up (P<0.05). In addition, the mean (SD) score of clinical syndrome in the Adler-Dracis group, was 173.1 (19.1) in the pre-test, 134.9(8.1) in the post-test, and 136.6(11.0) in the follow-up (P<0.05). However, the clinical syndrome scores in the control group showed no significant differences in three stages of pre-test 169.1(14.4), post-test 163.5(9.5) and follow-up 165.9 (11.7). The mean (SD) scores of Adler-Dreikurs intervention decreased significantly more compared with the parent-child method. Conclusion: The study showed that it is important to educate mothers based on two Parent-Child and Adler-Dreikurs approaches to reduce the clinical symptoms of children, and that the education of mothers based on Adler-Dreikurs approach was more effective. DOI: http://doi.org/10.22037/ch.v6i4.25341